Knowledge regarding Chronic Kidney Disease and its Prevention in Diabetic and Hypertensive Patients among Nurses - Mehta, Anita; Trikhatri, Chanak (Med Phoenix, 2025)
Introduction: Chronic kidney Disease is becoming a major global health problem. Knowledge regarding Chronic Kidney Disease and its prevention among diabetic and hypertensive clients have a significant importance in our society because renal health is unavoidable for a healthy body. The aim of this study is to assess the level knowledge regarding chronic kidney disease and its prevention in   diabetic and hypertensive cases among nurses.Materials and methods: A descriptive cross-sectional research study conducted at National Medical College Teaching Hospital, Birgunj, enrolling 101 participants involving the nurses of different departments. The total sample size was 101, using total enumerative sampling technique for sample selection. The ethical clearance letter was taken from the Institutional Review Committee of National Medical College and formal informed consent was also taken from all the participants. Data was organized in excel sheet in order for editing, classifying, coding and tabulating the information  and analyzed by using SPSS 20.0 in descriptive and inferential statistics. Results: This study comprising 101 participants found that 37% of respondents had a high level of knowledge, 46% had moderate level of knowledge, and 17% had a low level of knowledge regarding chronic kidney disease prevention in diabetic and hypertensive patients. The average age of the participants was 26 years with maximum belonging to PCL nursing (n=65, 64.4%) followed by BSc Nursing (n=21, 20.8%) and 15 participants (14.8%) were Bachelor of Nursing (BN). The results revealed no association between the respondents knowledge scores with age (p=0.17); educational qualifications (p=0.81); duration of experience (p=0.68).Conclusion: This study gives a conclusion that less numbers of nurses had good knowledge regarding the prevention of chronic kidney disease in diabetics and hypertensive patients. There is a need for formal teaching learning activities including trainings focusing on the different aspects of chronic kidney disease prevention as a good number of nurses are not having the sound knowledge regarding it. The training regarding the same should be mainstay part of understanding about the knowledge of kidney disease prevention.